2011
DOI: 10.1128/ec.00263-10
|View full text |Cite
|
Sign up to set email alerts
|

Orthologues of the Anaphase-Promoting Complex/Cyclosome Coactivators Cdc20p and Cdh1p Are Important for Mitotic Progression and Morphogenesis in Candida albicans

Abstract: The conserved anaphase-promoting complex/cyclosome (APC/C) system mediates protein degradation during mitotic progression. Conserved coactivators Cdc20p and Cdh1p regulate the APC/C during early to late mitosis and G 1 phase. Candida albicans is an important fungal pathogen of humans, and it forms highly polarized cells when mitosis is blocked through depletion of the polo-like kinase Cdc5p or other treatments. However, the mechanisms governing mitotic progression and associated polarized growth in the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 91 publications
2
28
0
Order By: Relevance
“…Our screen identified four candidates as regulators of genome stability in C. albicans. Null or conditional deletion mutants have been obtained and studied for three of these genes, CDC20 (43), RAD51 (44), and RAD53 (45), yet the role of these genes in genome integrity was never addressed, except for RAD53, whose deletion increases the frequency of LOH (16). Reports of C. albicans mutants overexpressing the four candidate genes could not be found in the literature.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our screen identified four candidates as regulators of genome stability in C. albicans. Null or conditional deletion mutants have been obtained and studied for three of these genes, CDC20 (43), RAD51 (44), and RAD53 (45), yet the role of these genes in genome integrity was never addressed, except for RAD53, whose deletion increases the frequency of LOH (16). Reports of C. albicans mutants overexpressing the four candidate genes could not be found in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the sustained presence of the Cdc20 protein could perturb genome integrity and our observation that overexpression of C. albicans CDC20 favors LOH, especially through chromosome loss when these types of events can occur, is consistent with this hypothesis. Conditional CDC20 deletion mutants of C. albicans have been characterized by Chou et al (43). Their work suggested that, similar to ScCDC20, CaCDC20 was important for the metaphase-to-anaphase transition and mitotic exit.…”
Section: Discussionmentioning
confidence: 99%
“…CDC20 encodes a protein that is required for the metaphase-to-anaphase transition and mitotic exit during the cell cycle. Depletion of Cdc20 in a mutant strain displaying resulted in highly polarized growth of yeast buds under yeast growth conditions but had no influence on serum-induced hyphal growth [55]. Further studies are required to investigate the association between Cdc20-mediated cell cycle progression and cell invasion.…”
Section: Resultsmentioning
confidence: 99%
“…4, Supp. 3) could also contribute to the defective phenotypes observed for the ILS1 conditional mutant in both yeast and hyphal forms as described for the lack of mitotic regulators 44 . Moreover, the metabolic activity of the ILS1 biofilm was considerably lower ( P < 0.01) compared to the WT (−/+DOX) and heterozygous biofilms.…”
Section: Discussionmentioning
confidence: 96%